Biometric Emigration Passes: Health Surveillance and Labour Control in the Indian Indenture Program - Dominica Prasad; Midori Ogasawara (Surveillance & Society, 2026)
Between 1834 and 1920, two million people migrated from India to other British colonies to work on plantations under indenture contracts (Kaladeen 2021). The Indian indenture program replaced slavery but bound workers to long-term, unfree labour in foreign lands. Britain developed complex institutions to mobilize and transport cheap labour power within and beyond its empire. Surveillance of indentured labourers was essential to the institutions, in which the “emigration pass” system played a key role in regulating the recruitment, registration, and migration of workers. Examining archival documents of emigration passes from India to Fiji, this article unpacks the hidden history of the Indian indenture program and analyzes the emigration pass as a tool for racializing surveillance embedded in the indenture system (Browne 2015). Emigration passes issued to migrant workers recorded a variety of personal information, including biometric data, such as fingerprints and bodily marks. While emigration passes declared clear consent by each worker to enter indenture, demarcating slavery, the passes also show that workers were subjected to intensive health surveillance, in which they were not only stripped naked in search of bodily marks but also assessed for signs of sexually transmitted infections and smallpox, and had their pulses, tongues, and general appearances checked (Mahase 2017). We argue that the emigration pass legitimized British officials’ access to indentured labourers’ bodies, transformed their previously indistinguishable bodies into identifiable information, and hid unfree realities of supposedly free labour.